Produção do espaço urbano e mercado imobiliário: a oferta de terrenos não edificados e imóveis residenciais urbanos em Ituiutaba (MG) - (:unkn) unknown (Universidade Federal de Goiás, 2016)
This dissertation analyzes the production of urban space and its joints starting the real estate market from the concrete reality investigated in the city of Ituiutaba (MG), contemplating the processes related to the marketing of unbuilt land and urban properties offered in newspaper classifieds. Considers, in this scope, the timeframe of 2000, 2005 and 2012. Thereby, we discussed about: production of urban space; producers agents of urban space and; real estate market. Constituted this analytical framework, our understanding turned to analysis of commercialization of urban real estate through of survey, mapping and collection of the variables available in the classified of real estate from the main local daily newspaper. Gradually, the Organization, interpretation and analysis of data, added to the bibliography studied and the information gathered in the field, allowed us a glimpse of recent changes in the production of urban space of Ituiutaba (Minas Gerais), above all, through the launch of new real estate developments, which redrew its municipal boundaries and promoted the spatial selectivity highlighting certain areas of the city with regard to potential real estate appreciation, such as the Southeast Sector.
Production of urban space and imobilario market: the supply of unbuilt land and urban residential properties in Ituiutaba (MG)
Keywords: Produção do espaço urbano; Mercado imobiliário; Ituiutaba (MG); Production of urban space; Imobilario market; CIENCIAS HUMANAS::GEOGRAFIA